The Release of ADP from Red Blood Cells - Rørvik, T. O; Holmsen, I; Stormorken, H (Thrombosis and Haemostasis, 1968)
The content of the adenine nucleotides, ADP and ATP, in whole blood from normals, patients with von Willebrand’s disease and diabetics was found to be equal. The hemolysis and AN-release from blood cells by contact with foreign surface were studied by passing blood through glass bead columns. The AN-release induced in this way was shown to be a hemolysis-related phenomenon, AN and hemoglobin were released in the same proportion as they were found within red cells. The hemolysis and AN-release induced in this way were nearly the same in blood from normals, patients with von Willebrand’s disease and diabetics.Thrombin did not induce hemolysis or release of AN from red blood cells, whereas the release of AN from platelets by thrombin was confirmed.